2018
DOI: 10.7324/jabb.2018.60304
|View full text |Cite
|
Sign up to set email alerts
|

Coleoptilar node - A season-independent explant source for in vitro culture in maize (Zea mays L.)

Abstract: In vitro plant regeneration is preliminary requisite in the process of obtaining transgenic plants. Somatic embryogenesis is the most frequently used method of in vitro plant regeneration in maize. In this study, a reliable and reproducible maize regeneration method has been standardized using mature embryos. Inspite, the immature embryos are most suitable explants for somatic embryogenesis, obtaining these explants continuously is a laborious and tedious process, especially in summer. Hence, alternate explant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Genotype is also critical and associated with the explant for in vitro growth and regeneration. Sridevi et al [19] reported that inbred line NM5884 is suitable for using IEs as explants, whereas another inbred line NM74C has been reported suitable for using coleoptilar node as an explant [45]. In the present study, it has been further confirmed that NM5884 is the most suitable genotype for using IEs not only for in vitro studies but also for genetic transformation in maize.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Genotype is also critical and associated with the explant for in vitro growth and regeneration. Sridevi et al [19] reported that inbred line NM5884 is suitable for using IEs as explants, whereas another inbred line NM74C has been reported suitable for using coleoptilar node as an explant [45]. In the present study, it has been further confirmed that NM5884 is the most suitable genotype for using IEs not only for in vitro studies but also for genetic transformation in maize.…”
Section: Discussionsupporting
confidence: 78%
“…As maize is an important crop with a wide range of utilization as food and fodder, extensive exploration of suitable conditions and materials for the development of the crop has been done. For in vitro studies and transformation, almost all the plant parts have been used viz., immature tassels [40], shoot tips [41,42], germinated split seeds [43], mature embryos [44], and coleoptile nodes [36,45]. Among all the explants of maize used, immature embryos were found to be the best explants in most of the studies [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation